The Influence of the Learning Environment on Student Achievement with Learning Motivation as a Mediating Variable for Students in Class XI SMKN 48 JAKARTA - Fitrilia Nurtamara; Ati Sumiati; Santi Susanti (Reflection: Education and Pedagogical Insights, 2023)
This study aims to determine the effect of Learning Environment on Learning Achievement with Learning Motivation as a mediating variable in class XI students of SMKN 38 Jakarta. The population in this study amounted to 286 students in grade XI of SMKN 48 Jakarta. In this study, researchers used research instruments with quantitative methods with a total of 167 respondents. Data collection was carried out by distributing questionnaires with random sampling. The results of this study indicate that 1) Learning Environment has a positive and significant direct influence on Learning Motivation; 2) Learning Environment has a positive and significant direct influence on Learning Achievement; 3) There is no indirect effect between Learning Environment and Learning Achievement through Learning Motivation. The variables used in this study can be said to be few, so it can still be added with other variables such as interest, discipline, learning methods, and learning facilities. The sample in this study can also be said not to represent all students of SMKN 48 Jakarta because it only examines class XI.